Ethnic entrepreneurship structure and process - Stiles, Curt H.; Galbraith, Craig (JAI, 2003)
The papers in this volume, the fourth in the series International Research in the Business Disciplines, provide a broad survey of the nature and scope of entrepreneurship within ethnic groups. Of particular interest, the contributors address the role of ethnic entrepreneurship in shaping the structure of modern economies. Ethnicity has heretofore been given less attention in entrepreneurship research than its importance might seem to warrant due largely to the prevalence of the assimilation hypothesis: the assumption that everyone, without regard to ethnicity, works as a producer in the general economy and buys as a consumer from the general economy. The economic uniformity implied by this assumption invites critical comment. In five parts, the collection explores aspects of ethnic entrepreneurship as both part of the structure of the general economy and in terms of the process of movement toward or away from assimilation. The collection features a comprehensive new study of ethnic entrepreneurship by Ivan Light. Additional highlights include examination of structural variables and abstract models, analysis of the components of the definition of ethnicity, consideration of impacts on assimilation, and finally, the relevance of access to financial capital provided by the general economy. Researchers are bringing new insights and methods to the phenomena of ethnic producers and consumers of ethnic products dependent on ethnic market mechanisms. This volume makes a significant contribution to this research.
Keywords: Minority business enterprises.; Entrepreneurship.; Businesspeople -- Social conditions.; Minorities -- Economic conditions.; elektronické knihy; electronic books